Characterisation of superficial corneocyte properties over category I pressure ulcers: Insights into topographical and maturation changes - Évora, Ana S.; Abiakam, Nkemjika; Zhang, Zhibing; Johnson, Simon A.; Adams, Michael J.; Bader, Dan L.; Worsley, Peter R. (Journal of dermatological science, 2023)
Pressure ulcers (PUs) are chronic wounds that are detrimental to the quality of life of patients. Despite advances in monitoring skin changes, the structure and function of skin cells over the site of pressure ulcers are not fully understood. The present study aims to evaluate local changes in the properties of superficial corneocytes in category 1 PU sites sampled from a cohort of hospitalised patients. Cells were collected from a PU-compromised site and an adjacent control area and their topographical, maturation and mechanical properties were analysed. Corneocytes at the PU-compromised site were characterised by higher levels of immature cornified envelopes (p < 0.001) and greater amounts of desmoglein-1 (corneodesmosomal protein) (p < 0.001) compared to the adjacent control area. The cells at the control site presented the typical ridges-and-valleys topographical features of sacrum corneocytes. By contrast, the PU cells presented circular nano-objects at the cell surface, and, for some patients, the cell topography was deformed. CEs at the PU site were also smaller than at the control site. Although differences were not observed in the mechanical properties of the cells, those of the elderly patients were much softer compared with young subjects. This is the first study investigating the changes in corneocyte properties in category I pressure ulcers. Superficial cells at the PU sites showed altered topographical and maturation characteristics. Further studies are required to elucidate if these changes are a consequence of early loss of skin integrity or a result of mechanical and microclimate insults to the skin surface. •This is the first cohort study that has investigated the changes in the properties of corneocyte over category I PUs.•Superficial cells at the PU sites showed altered topographical and maturation characteristics.•Topographic features in the PU sites included the presence of circular nano-objects, as well as increased levels of desmoglein-1 in the central surface regions of the cells and an increase in the levels of immature cornified envelopes.